PENGEMBANGAN MEDIA KARTU KATA UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PADA ANAK KELOMPOK B DI TK DHARMA WANITA AIK MUAL - Ria Anjelina; Fahruddin; Ni Luh Putu Nina Sriwarthini; Ika Rachmayani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to develop word card media to improve reading skills in group B children. This type of research uses Research and Development research. The subjects in this research were 6 children consisting of 3 boys and 3 girls at the Dharma Wanita Aik Mual Kindergarten. The data collection methods used are observation, questionnaires and documentation methods. Data analysis uses descriptive qualitative analysis. The stages in the word card media game are: 1. The child is shown a picture of the word card media, 2. The child pairs the word cards that match the picture, then the child pins the word cards to the flannel board, 3. The child says the name of the letter on the word card, 4. Children read the name of the word card according to the picture. The results of this research indicate that the word card media is declared suitable for use in learning with the percentages generated based on product tests by experts. Reading skills using word cards as media for group B children at Dharma Wanita Aik Mual Kindergarten experienced an increase in development, namely in Development Stage I it was 57.2% (Developing According to Expectations) while in Development Stage II it was 93.2% (Developing Very Well ). The achievement of reading skills in group B children using word card media increased by 36%. It can be concluded that the development of the word card media developed can improve the reading skills of group B children at the Dharma Wanita Aik Mual Kindergarten.